Technical success and safety of peripherally inserted central catheters in the great saphenous and anterior accessory great saphenous veins. Issue 2 (March 2022) - Jin, Mauricio F; Thompson, Scott M; Comstock, Ann C; Levy, Emily R; Reisenauer, Christopher J; McPhail, Ian R; Takahashi, Edwin A
Background: Peripherally inserted central catheters (PICC) are occasionally placed in the great saphenous vein (GSV) and anterior accessory great saphenous vein (AAGSV) in patients with inadequate upper extremity veins or contraindications to upper extremity placement. Outcomes on the placement of PICCs in these veins are limited. Objectives: This study aimed to determine technical success and safety of GSV/AAGSV PICCs. Materials and methods: This is a retrospective study that reviewed all GSV/AAGSV PICC placements between January 2011 and December 2019. A total of 29 PICC placements procedures were identified. The electronic medical record was queried for demographic, procedural, and complication data. Technical success was defined by whether the vein could be accessed and a PICC could be placed. Catheter-associated infections, dislodgement or migration, malfunction, and PICC-associated thrombosis were recorded. Results: Technical success of placement was 100%. Twenty-one (72%) catheters were placed in the GSV in the mid to upper thigh and eight (28%) were placed in the AAGSV. The median PICC dwell time was 13 days with a range of 3–155 days. PICC-associated complications occurred after 11 (37.9%) placements. Line associated infection was the most common complication (17.2%). Conclusion: Due to a high complication rate, GSV/AAGSV PICC placement should be considered only when upper extremity or cervical PICC placement is not feasible or contraindicated.